2013
DOI: 10.1016/j.jpain.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Pain Management Practices: The Role of Physician Sex on Chronic Low-Back Pain Assessment and Treatment Prescriptions

Abstract: The impact of physician sex on dimensions of medical care such as treatment prescriptions and referrals has been underexplored, especially in a pain context. Also, few studies have analyzed whether physicians sex moderates the influence of patients' or clinical situations' characteristics on pain management practices or its mediating processes. Therefore, our goal was to explore whether physician sex moderates the: a) effects of patient's (distressed) pain behaviors and diagnostic evidence of pathology (EP) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
1
34
1
Order By: Relevance
“…Thirteen articles [ 6 , 8 , 22 , 53 , 69 71 , 75 , 77 , 80 – 82 , 84 ] in this review classified “medically unexplained” conditions in 19 different ways, for example, as pain without organic, observable, and objective symptoms [ 6 ]. The classifications are listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles [ 6 , 8 , 22 , 53 , 69 71 , 75 , 77 , 80 – 82 , 84 ] in this review classified “medically unexplained” conditions in 19 different ways, for example, as pain without organic, observable, and objective symptoms [ 6 ]. The classifications are listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…71 Several studies suggest patient and provider gender may interactively contribute to variation in ED provider pain treatment practices. For example, Bernardes et al found that gender of the treating practitioner influenced pain management practices in the treatment of back pain in clinical vignettes, 72 and another study found that nurses were more likely than physicians to rate pain higher and more willing to administer opioid analgesics to male patients. 73 Marquie et al found a three-way interaction among physician expertise, physician gender, and patient gender.…”
Section: Resultsmentioning
confidence: 99%
“…Physician-patient interactions require good interpersonal skills to elicit and provide core information, and there are gender differences in the nonverbal behaviours exhibited during such transactions [26]. The relevance of gender context becomes even more interesting when combined with the knowledge that patient gender affects how health care providers assess and treat pain [6,28,46,55]. However, such studies are few in number, and there are inconsistencies [33,57,76].…”
Section: Gender Differences In the Nonverbal Communication Of Painmentioning
confidence: 99%